Analytical assessment and nutritional adequacy of school lunches in Sintra’s public primary schools - Nogueira, Telma (2021)
School meals present several cost benefits over time in the short, medium, and long term for individuals and society. This cross-sectional study aims to analyze the nutritional composition and evaluate the adequacy of school lunches. One hundred and fifty-eight samples were collected and analyzed from 10 primary schools in Sintra’s municipality, served during one week. On average, energy (27.7% daily energetic requirements) and carbohydrate (48.1%) contents did not reach the reference values, and the content of protein (19.5%) exceeded the reference value (p < 0.05). The mean total fat (28.8%) and saturated fatty acids (5.4%) content complied with the recommendations. The mean salt (1.7 g) and dietary fiber (8.3 g) content exceeded the reference value but did not differ significantly from the recommendations. Addressing school canteens is crucial, not only in a nutritional approach, but also as an opportunity to achieve healthier, sustainable, and accessible food systems, aligned with the Sustainable Development Goals 2030. We highlighted the importance of evaluating evidence-based practices and disseminated practice-based evidence regarding the adequacy of school lunches.